Critical thinking of field dependent student’s in problem solving - Dian Septi Nur Afifah; Ria Lestari Ningrum (Universitas Islam Negeri Maulana Malik Ibrahim, 2018)
The purpose of this research is to describe the characteristics of the critical thinking of field-dependent cognitive style students in problem-solving. This research is qualitative research. Research subjects are students who have field-dependent cognitive style in class VIII SMP Negeri 1 Boyolangu, Indonesia. Data collection is GEFT test, math problem test, and interview. The results showed that strong field dependent students in mathematics problem solving aren't good at understanding the problem. At the implementing stage, the solution stage according to the previous plan. The problem-solving plan depends on the formulation of the problem that students found, students are less precise in carrying out the problem-solving. Students do not check again the answer. Critical thinking of weak field dependent students is not good in understanding the problem, and information in the problem is quite good. At the making solution plan stage, students do not write down what is known and asked and less able to express a solution plan clearly and logically with the problem. At the implementing stage, the solution plan is by the previous plan. The problem-solving plan depends on the problem formulation of the problem that students found, so students are less precise in carrying out the problem-solving. Students do not check again the answers.